A long-term follow-up study of the clinical and radiographic outcome of distal trochanteric transfer in Legg-Calvé-Perthes' disease following varus derotational osteotomy. (July 2017) - Shohat, N.; Gilat, R.; Shitrit, R.; Smorgick, Y.; Beer, Y.; Agar, G.
Abstract : Aims: To assess the long-term effect of distal trochanteric transfer (DTT) on the clinical and radiographic outcomes of patients with Legg-Calvé-Perthes' disease (LCPD) following a varus derotational osteotomy (VDRO). Patients and Methods: For this single centre cross-sectional retrospective study we analysed the data of 22 patients (24 hips) with LCPD who had greater trochanteric overgrowth (GTO), following a VDRO performed in our institution between 1959 and 1983. GTO was defined as an articular trochanteric distance (ATD) of < 5 mm. We compared the radiographic and clinical outcomes of patients who underwent DTT for GTO (ten patients, ten hips) with those who did not (12 patients, 14 hips). Age at presentation was 6.9 years (4 to 10) and 8.0 years (3.2 to 12) respectively. Symptoms associated with the hip and general quality of life were assessed using the Harris hip score (HHS) and the Short Form (SF)-36 questionnaires. Results: At long-term follow-up of the DTT group, the ATD was 21.7 mm (standard deviation (sd ) 9.8) and the centro-trochanteric distance (CTD) was 13.8 mm (sd 8.3). In the control group the ATD was -0.6 mm (sd 7.8) and the CTD was 32.5 mm (sd 10.2). These differences were statistically significant (p < 0.001). The mean HHS and SF-36 scores were 68.4 (sd 25.0) and 62.0 (sd 27.7) for the DTT group and 73.2 (sd 24.2) and 73.3 (sd 21.5) for the control group, respectively. There was no statistically significant difference in the HHS (p = 0.63) or SF-36 score (p = 0.25). There were four patients who had undergone hip arthroplasty in the DTT group (40%) and one patient (7.1%) in the control group (p = 0.07). The mean age at the time of arthroplasty was 45.3 years (42.1 to 56.5) and 43.6 years respectively. Six patients in the DTT group suffered from moderate to severe osteoarthritis (Tönnis grade 2 or 3) compared with eight patients in the control group (60% versus 57.1%, p = 0.61). Conclusion: Although DTT improved the radiographic results in the long-term follow-up of patients with GTO following VDRO, there was no clinical benefit seen in the HHS, SF-36 or incidence of osteoarthritis compared with patients who had not undergone DTT. Cite this article: Bone Joint J 2017;99-B:987–92.